Motion extrapolation in the flash-lag effect depends on perceived, rather than physical speed. (April 2022) - Yook, Jane; Lee, Lysha; Vossel, Simone; Weidner, Ralph; Hogendoorn, Hinze
Highlights: Perceived speed of a moving object can alter, while its physical speed is constant. Illusory changes in perceived speed modulate the magnitude of the flash-lag effect. Changes in the illusion could be explained by changes in perceived speed. Role of perceived speed supports motion extrapolation account of the flash-lag effect. Abstract: In the flash-lag effect (FLE), a flash in spatiotemporal alignment with a moving object is misperceived as lagging behind the moving object. One proposed explanation for this illusion is based on predictive motion extrapolation of trajectories. In this interpretation, the diverging effects of velocity on the perceived position of the moving object suggest that FLE might be based on the neural representation of perceived, rather than physical, velocity. By contrast, alternative explanations based on differential latency or temporal averaging would predict that the FLE does not rely on such a representation of perceived velocity. Here we examined whether the FLE is sensitive to illusory changes in perceived speed that result in changes to perceived velocity, while physical speed is constant. The perceived speed of the moving object was manipulated using revolving wedge stimuli with variable pattern textures (Experiment 1) and luminance contrast (Experiment 2). The motion extrapolation interpretation would predict that the changes in FLE magnitude should correspond to the changes in the perceived speed of the moving object. In the current study, two experiments demonstrated that perceived speed and FLE magnitude increased in the dynamic pattern relative to the static pattern conditions, and that the same effect was found in the low contrast compared to the high contrast conditions. These results showed that manipulations of texture and contrast that are known to alter judgments of perceived speed also modulate perceived position. We interpret this as a consequence of motion extrapolation mechanisms and discuss possible explanations for why we observed no cross-effect correlation.